2016
DOI: 10.1186/s40478-016-0382-8
|View full text |Cite
|
Sign up to set email alerts
|

Microglial neuroinflammation contributes to tau accumulation in chronic traumatic encephalopathy

Abstract: The chronic effects of repetitive head impacts (RHI) on the development of neuroinflammation and its relationship to chronic traumatic encephalopathy (CTE) are unknown. Here we set out to determine the relationship between RHI exposure, neuroinflammation, and the development of hyperphosphorylated tau (ptau) pathology and dementia risk in CTE. We studied a cohort of 66 deceased American football athletes from the Boston University-Veteran’s Affairs-Concussion Legacy Foundation Brain Bank as well as 16 non-athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
235
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 225 publications
(257 citation statements)
references
References 38 publications
20
235
2
Order By: Relevance
“…44,45 RHI intensity and duration and their interaction with variables like age and genetics (e.g., APOE e4 ) 3,7 may be more important determinants of pathology. 3,39 In contrast, our findings that show a relationship between AFE and age of symptom onset are consistent with previous research in living former amateur and professional tackle football players that linked younger AFE to tackle football, before age 12 in particular, with worse cognitive, behavior, and mood outcomes. 11,14 The clinical presentation of CTE seems to involve early-life behavioral/mood symptoms and/or later-life cognitive impairment.…”
Section: Discussionsupporting
confidence: 92%
“…44,45 RHI intensity and duration and their interaction with variables like age and genetics (e.g., APOE e4 ) 3,7 may be more important determinants of pathology. 3,39 In contrast, our findings that show a relationship between AFE and age of symptom onset are consistent with previous research in living former amateur and professional tackle football players that linked younger AFE to tackle football, before age 12 in particular, with worse cognitive, behavior, and mood outcomes. 11,14 The clinical presentation of CTE seems to involve early-life behavioral/mood symptoms and/or later-life cognitive impairment.…”
Section: Discussionsupporting
confidence: 92%
“…This is further supported by recent in vivo brain imaging studies of football athletes, which revealed evidence of chronic microglial activation (Cherry et al, 2016; Coughlin et al, 2017). Interestingly, research in murine AD models has shown that neuroinflammatory cytokines and reactive microglia can promote tau pathology and contribute to the spread of pTau, which might explain the link between TBI-induced inflammation and CTE (Ghosh et al, 2013; Maphis et al, 2015).…”
Section: Introductionsupporting
confidence: 64%
“…Second, injury-induced severing of neuronal axons may cause tau to dissociate from microtubules, which could facilitate subsequent tau aggregation [35]. Third, the chronic inflammation that results from brain injuries likely exacerbates and sustains the acute tauopathy that occurs shortly after injury [36]. …”
Section: Stimulators Of Pathogenic Tau Formationmentioning
confidence: 99%